A methods engineering study on CNJ Plastics Manufacturing Corporation - Avena, Cherrie May; Espiritu, Kart Pearson (Diliman, Quezon City College of Engineering, 2005)
The objective of this study is to apply methods engineering to an existing manufacturing company. The proponents of the study chose CNJ Plastics Manufacturing Corporation as project site, which particularly manufactures polypropylene and polyethylene plastic bags. The scope of the study lies within the production system and factory operations within the company. The company was documented in detail through interviews and actual observations done during plant visits. A close examination of processes helped the group identify significant data that can be used for further study. Problem identification and analysis follow the documentation. The proponents chose three major problems, waste, bottleneck operations and lack of supervision, where methods engineering can be applied within the control of the company. Alternative solutions to the problems were generated using the data gathered. Brainstorming helped the group evaluate the alternatives that results to recommendations to problems addressed in the study. The recommendations include, statistical analysis of operations using multiple linear regression, new layout and improvement of methods and working conditions. These recommendations, when implemented, will result in an increase in productivity and efficiency of workers. The study proved the usefulness of methods engineering techniques in addressing problems in a manufacturing company. However, techniques provided were just few of the many. Thus, further study to validate the results of the study should be done in particular.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis